Recruiting participants for focus groups in health research: a meta-research study - Jonas Lander; Simon Wallraf; Dawid Pieper; Ronny Klawunn; Hala Altawil; Marie-Luise Dierks; Cosima John (BMC Medical Research Methodology)
Abstract Background Focus groups (FGs) are an established method in health research to capture a full range of different perspectives on a particular research question. The extent to which they are effective depends, not least, on the composition of the participants. This study aimed to investigate how published FG studies plan and conduct the recruitment of study participants. We looked at what kind of information is reported about recruitment practices and what this reveals about the comprehensiveness of the actual recruitment plans and practices. Methods We conducted a systematic search of FG studies in PubMed and Web of Science published between 2018 and 2024, and included n = 80 eligible publications in the analysis. We used a text extraction sheet to collect all relevant recruitment information from each study. We then coded the extracted text passages and summarised the findings descriptively. Results Nearly half (n = 38/80) of the studies were from the USA and Canada, many addressing issues related to diabetes, cancer, mental health and chronic diseases. For recruitment planning, 20% reported a specific sampling target, while 6% used existing studies or literature for organisational and content planning. A further 10% reported previous recruitment experience of the researchers. The studies varied in terms of number of participants (range = 7–202) and group size (range = 7–20). Recruitment occurred often in healthcare settings, rarely through digital channels and everyday places. FG participants were most commonly recruited by the research team (21%) or by health professionals (16%), with less collaboration with public organisations (10%) and little indication of the number of people involved (13%). A financial incentive for participants was used in 43% of cases, and 19% reported participatory approaches to plan and carry out recruitment. 65 studies (81%) reported a total of 58 limitations related to recruitment. Conclusions The reporting of recruitment often seems to be incomplete, and its performance lacking. Hence, guidelines and recruitment recommendations designed to assist researchers are not yet adequately serving their purpose. Researchers may benefit from more practical support, such as early training on key principles and options for effective recruitment strategies provided by institutions in their immediate professional environment, e.g. universities, faculties or scientific associations.